2020
DOI: 10.4028/www.scientific.net/msf.1004.547
|View full text |Cite
|
Sign up to set email alerts
|

Development of High-Quality Gate Oxide on 4H-SiC Using Atomic Layer Deposition

Abstract: A systematic post-deposition annealing study on Silicon Carbide (SiC) metal-oxide-semiconductor capacitors (MOSCAPs) using atomic layer deposition (ALD)-deposited silicon dioxide (SiO2) layers was carried out. Anneals were done in oxidising (N2O), inert (Ar) and reducing (H2:N2) ambients at elevated temperatures from 900°C to 1300°C for 1 hour. Electrical characterisation results show that the forming gas treatment at 1100°C reduces the flatband voltage to 0.23 V from 10 V for as-deposited SiO2 layers. The den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Oxides formed using ALD and thermal oxidation were considered. A FG postdeposition anneal was carried out on ALD-deposited samples since this process has recently shown a big improvement in terms of electrical parameters and interface quality when compared to as-deposited ALD silicon dioxide and thermal oxide [16,17].…”
Section: Electrical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxides formed using ALD and thermal oxidation were considered. A FG postdeposition anneal was carried out on ALD-deposited samples since this process has recently shown a big improvement in terms of electrical parameters and interface quality when compared to as-deposited ALD silicon dioxide and thermal oxide [16,17].…”
Section: Electrical Resultsmentioning
confidence: 99%
“…Following deposition, one set of samples (freestanding 3C-SiC, 3C-SiC on Si and 4H-SiC) was left as-deposited, and a second set of samples was loaded into a high-temperature anneal furnace, where they were annealed in forming gas (FG, 5% H 2 in 95% N 2 ) for 1 h with a gas flow of 5 slm and a temperature of 1100 • C, as this process has been reported to improve the interface on 4H-SiC/SiO 2 MOSCAPs [16].…”
Section: Electrical Resultsmentioning
confidence: 99%
“…Also, Figure 2 shows (a) a typical set of C-V responses as well as (b) density of interface trap, DIT, levels, which were plotted over the trap energy level position, ET, below the conduction band edge, EC. All the investigated MOSCAPs had flatband voltage values close to zero, with the ALD-deposited oxide showing the lowest level, averaging 0.63 V. For benchmarking, the electric performance of ALD as-deposited SiO2 layers has been published by the authors before and can be found in [5,7], where the asdeposited layers showed average flatband voltage values of >8 V. Here, the ALD-deposited oxide that subsequently underwent a PDA in N2O ambient also had a very tight distribution of hysteresis voltages and frequency dispersions, which averaged at 0.28 V and 0.11 %.dec -1 respectively. The LPCVD-deposited and thermally grown oxide layers only show marginal flatband voltage deviations from the ALD-deposited layers, averaging 1.13 V and 0.96 V respectively.…”
Section: Capacitance-voltage Investigationmentioning
confidence: 99%
“…They also do not consume any of the SiC material, meaning that the interface is less likely to be carbon-rich after deposition [3]. However, the electrical properties of as-deposited SiO2 layers are poor [3,4], and, after their deposition on SiC, a post-deposition anneal (PDA) typically follows in a nitrogen-containing ambient, such as nitric (NO) or nitrous oxide (N2O) at temperatures above 1,100°C [5]. In this work, we present the improvement brought about by deploying ALD-deposited SiO2 layers which were post-deposition annealed in forming gas (FG) and N2O ambient.…”
Section: Introductionmentioning
confidence: 99%